2018
DOI: 10.1186/s12889-018-5080-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for first-time acute myocardial infarction patients in Trinidad

Abstract: BackgroundThe relative importance of coronary artery disease (CAD) risk varies globally. The aim of this study was to determine CAD risk factors for acute myocardial infarction (AMI) among patients in public health care institutions in Trinidad using a case–control type study design.MethodsThe sample comprised 251 AMI patients hospitalized between March 1, 2011 and April 30, 2012 and 464 age- and sex-matched non-AMI patients with no terminal or life-threatening illness and who did not undergo treatment for CAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 41 publications
2
15
0
1
Order By: Relevance
“…The most common risk factors were age above 45 years, diabetes mellitus, hypertension, obesity, physical inactivity, and smoking. These traditional risk factors for MI affected more than one-third of the surveyed patients, a finding similar to what has been shown by Framingham Heart study (17) the INTERHEART study (18), and several previous studies (19)(20)(21). The study identified that 6.8% to 22.3% of the subjects represented a high risk group, who had three of more risk factors for MI.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The most common risk factors were age above 45 years, diabetes mellitus, hypertension, obesity, physical inactivity, and smoking. These traditional risk factors for MI affected more than one-third of the surveyed patients, a finding similar to what has been shown by Framingham Heart study (17) the INTERHEART study (18), and several previous studies (19)(20)(21). The study identified that 6.8% to 22.3% of the subjects represented a high risk group, who had three of more risk factors for MI.…”
Section: Discussionsupporting
confidence: 86%
“…While age is a well-known risk factor for MI, we found a considerable proportion of young adults (<45 years) suffering from MI. Previous research has pointed to the increasing incidence of MI among people younger than 45 years (20). These findings are concerning, as having MI at such age can have negative impact on social, psychological (22), and productivity of the patients (23), in addition to the quality of life of patients and their relatives (24) and related economic consequences (25).…”
Section: Discussionmentioning
confidence: 99%
“…Acute coronary syndrome (ACS) has been established to represent a consequence of atherosclerosis, with preventable and non-preventable risk factors that have been identified to lead to the onset of acute myocardial infarction (1,2). Atherosclerosis is a chronic inflammatory process in the middle arterial intima for which the Creactive protein (CRP), an acute-phase protein secreted during the inflammatory stimulus, has been shown to be an independent predictor of coronary artery disease (CAD) (3).…”
Section: Introductionmentioning
confidence: 99%
“…The common cardiovascular diseases that seriously affect human health include hypertension, coronary artery disease, and chronic heart failure, which may result from dysfunction of normal endothelial cell homeostasis [1]. Endothelial cell dysfunction has been shown to be the basis of the pathogenesis of cardiovascular disease [2].…”
Section: Introductionmentioning
confidence: 99%